A Stateless Neighbour-Aware Cooperative Caching Protocol for Ad-Hoc Networks - Miranda, Hugo (2005)
Replication of data items among different nodes of a Mobile Ad-Hoc Network (MANET) is an efficient technique to increase data availability and improve access latency. This paper proposes a novel algorithm to distribute cached data items among nodes in a MANET. The algorithm combines a probabilistic approach with latency constraints such as the distance from both the source and the clients of the data item. In most scenarios, our approach allows any node to retrieve a data item from a nearby neighbour (often, just one hop away). The paper describes the algorithm and provides its performance evaluation for several different network configurations